A survey of combinatorial theory - Bose, R. C. (Raj Chandra), 1901-1987; Srivastava, Jagdish Narain, 1933-; Harary, Frank; Rao, C. Radhakrishna (Calyampudi Radhakrishna), 1920-2023; Rota, Gian-Carlo, 1932-1999; Shrikhande, S. S. (Sharadchandra Shankar), 1917- (North-Holland Publishing Company, 1973)
The papers included in this volume were solicited and presented at a symposium in honor of Professor R. C. Bose in 1971, who has been active in mathematics and statistics since 1926. While his interest in coding theory is recent, it is expected to continue as he remains active as a mathematician.